The Events City: Sport, Culture, and the Transformation of Inner Melbourne, 1977–2006 - O’Hanlon, Seamus (Urban History Review / Revue d'histoire urbaine, 2009)
AbstractIn 2006 Melbourne, Australia, played host to an almost monthly lineup of major international sporting and cultural events: the Australian Open Tennis tournament, the Commonwealth Games and associated cultural festival, a Formula One Grand Prix, an International Flower and Garden Show, an arts festival, and what is billed as the third largest comedy festival in the world. Almost all of these events were staged primarily in a revitalized region within a five-kilometre radius of the city centre, and all—bar the Commonwealth Games—are annual events, part of a deliberate economic and tourism strategy that attempts to sell Melbourne as an “events city.” This paper charts the emergence of this events strategy and argues that, rather than being a phenomenon of the 1990s as is often assumed, its origins lie in the early 1980s and was a deliberate response to deindustrialization, urban decay, and “crisis” in the inner Melbourne economy in the 1970s. The paper recognizes the many successes of this economic policy but raises questions about a policy that adds to a growing economic gap between the now prosperous, gentrified inner city and the increasingly marginalized outer zones of the metropolis.